Cuentos infantiles y el desarrollo del lenguaje oral en niños y niñas de cinco años de la Institución Educativa Inicial N° 344 Mi Primer Aprendizaje, distrito de Punchana 2022 - Amasifuen Amasifuen, Connie Katherine (2024)
The present research is titled "Children's stories and oral language development in five year-old boys and girls of the Initial Educational Institution No. 344 - My first learning, Punchana district, Iquitos - 2022, the general research objective was to determine the relationship of children's stories in the development of oral language in five-year-old boys and girls of the Initial Educational Institution N°344, My First Learning Punchana, Iquitos - 2022, for this reason a quantitative investigation was established, oriented to the descriptive, correlational type, focusing on a non-experimental design, on a student population of 90 five-year-old students, using non-probabilistic sampling, demonstrating that children's stories contribute to the improvement of language development, also that both study variables are significantly relational, allowing a constructive relationship between the study variables. After applying the data collection instruments developed with the purpose of obtaining valuable information from the research, it was found that a high percentage of students have appropiate level of reading narrative texts, as well as that applying comprehensive reading procedures allows for improvement. significantly the development of oral language. using for this Kendall's Tau-b =0.835; Approximate significance = 0.001, after applying the inferential analysis procedure it was possible to demonstrate that the level of application of children's stories increases and also benefits the development of oral language in five year-old boys and girls of the I.E.I. N°344, My First Punchana Learning. The research concludes by stating that the application of children's stories in the development of language is important, as well as the strengthening of productive actions that guarantee the normal development of oral language supported by narrative texts. Likewise, it recommends establishing procedures for planning and executing actions that help improve reading comprehension, as well as the development of oral language in boys and girls at the initial level.